TEACHERS’ FEEDBACK USED IN LEARNING ENGLISH PROCESS AT SMAN 1 SUNGAI TARAB - Riyadi Saputra (Ristekdik : Jurnal Bimbingan dan Konseling, 2017)
The use of feedback in learning English process is interesting to be analyzed. Although it does not add much to the proportional explaining and giving instruction, but it still has much contribution to learning English process. This paper explores the teachers’ feedback (content and corrective feedbacks) in learning English process at SMAN 1 Sungai Tarab. Data were collected throughobservation and audio recording which involved 5 English teachers. All lessons were recorded and transcribed. The analysis of the transcripts revealed that almost all the types of content feedback were utilized by the teachers. And there were two types of corrective feedback neglected by the teachers. It is recommended that stakeholder of education or government should conduct some seminars related to the use of content and corrective feedbacks.Key words: Teacher Talk, Teachers’ Feedback, Learning Process.